Constellation Terms in Gorontalo Oral Tradition: An Ethnographic Study - Olin Harun; Harto S. Malik; Rahman Taufiqrianto Dako (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates constellation terms in the oral tradition of the Gorontalo community and examines their socio-cultural functions through Dell Hymes’s ethnography of communication. Using a descriptive qualitative approach, the study analyzed documented oral-tradition data consisting of a traditional star-calendar transcript and explanatory narratives related to constellation terminology. The analysis employed Hymes’s SPEAKING model to interpret the communicative context, symbolic meanings, and cultural functions of constellation discourse. The findings reveal that terms such as Ewela, Maluo, Otoluwa, Tadala, Pahi, and Totokia function not merely as names of star groupings, but also as ecological markers guiding agricultural activities, seasonal prediction, maritime practices, and other social actions. These constellation terms additionally operate as cultural symbols representing collective memory, ecological experience, caution, hope, and local environmental knowledge. The study further demonstrates that constellation discourse remains important in preserving indigenous ecological literacy and sustaining cultural identity within contemporary Gorontalo society amid modernization and generational change. The findings contribute to ethnolinguistics, cultural preservation, and indigenous ecological knowledge studies by showing that language in oral tradition functions not only to communicate information, but also to organize, interpret, and transmit local knowledge across generations.